Aluminum nitride ceramic sealing ring and preparation method thereof

By using the preparation method of aluminum nitride ceramic sealing ring, combined with the combination of aluminum nitride mixed powder and specific binder, the problems of low strength and high porosity of ceramic sealing ring are solved, and high density and low porosity are achieved Product preparation improves product performance and production efficiency.

CN119241253AInactive Publication Date: 2025-01-03FUJIAN HUAQING ELECTRONICS MATERIAL TECH

Patent Information

Application Number
CN202411759507.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ceramic sealing rings have low strength in green bodies during the production process, which are prone to defects such as collapse and cracking, and have high internal porosity, which cannot meet the high-demand product performance.

Method used

Using the preparation method of aluminum nitride ceramic sealing ring, using a binder of aluminum nitride mixed powder with paraffin, microcrystalline wax, high-density polyethylene, polypropylene and stearic acid and other materials, through ball milling, refining, crushing, Injection molding, degreasing, glue discharge and sintering are used to form high-density and low porosity products.

Benefits of technology

It improves the strength and conformity of the green body, reduces defects, enhances the dimensional accuracy and airtightness of the product, extends the service life, and improves mass production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, in particular to an aluminum nitride ceramic sealing ring and a preparation method thereof.The aluminum nitride ceramic sealing ring is prepared from, by weight, 83-85 parts of aluminum nitride mixed powder and 15-17 parts of binder; the aluminum nitride mixed powder comprises the following materials in parts by weight: 80-85 parts of aluminum nitride powder, 3-7 parts of yttrium oxide and 1-2 parts of a dispersing agent; the binder comprises the following materials in parts by weight: 50-60 parts of paraffin, 3-6 parts of microcrystalline wax, 20-30 parts of high density polyethylene, 8-15 parts of polypropylene and 3-6 parts of stearic acid. The formed green body is high in strength, and the problems of collapse, cracking and the like caused by low strength of the green body can be solved; the sintering deformation is small, the size precision is high, the internal porosity is low, and the product performance is greatly improved; and the mass production efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to an aluminum nitride ceramic sealing ring and a preparation method thereof. Background Art

[0002] In recent years, new energy vehicles have developed rapidly, and the demand for various important parts has increased. Ceramic sealing rings are an important part of new energy electric vehicles. This small electronic ceramic ring, called "new power battery ceramic sealing connector", is used in new energy electric vehicles to form a sealed conductive connection between the power battery cover and the pole. Secondly, ceramic sealing rings are also widely used in batteries. They are located under the battery cover. Their function is to ensure that the battery has good air tightness, prevent electrolyte leakage, and provide a good airtight environment for the internal reaction of the battery. At the same time, when the battery cover is pressed down, it can also play a decompression buffer role to ensure the normal operation of the internal components of the battery, providing important guarantees for the battery life and safety. At present, most of the ceramic sealing rings on the market are produced by dry pressing. The production process is simple, but the green strength is low. After sintering, there are many pores inside the blank. For some product applications with high use requirements, the results are not satisfactory, the strength is insufficient, and the service life is short. Ceramic powder injection molding is a new process for preparing ceramic parts developed by combining polymer injection molding method and ceramic preparation process. The density of the formed blank is uniform, the dimensional accuracy is high, the internal porosity of the product after sintering is low, the strength is high, and the batch production efficiency is high, which is very suitable for products with high requirements. The injection molding process mainly includes the steps of ball milling, mixing, crushing, injection, degreasing, debinding, and sintering. Among them, the preparation of injection feed is particularly critical. The selection, treatment, composition and ratio of the powder will directly affect the various process links of the product in injection molding. The feed must have good fluidity and uniformity to fill the mold cavity; the green strength of the injection product must be good and the shape retention is good, so it is not easy to deform and affect the dimensional accuracy. The ceramic sealing ring prepared by the existing dry pressing molding process has low green strength during the pressing, debinding and sintering process, and the product is prone to collapse, cracking and other defects, resulting in a low qualified rate of the produced products, and the internal pores cannot meet the high requirements of customers. Summary of the invention

[0003] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide an aluminum nitride ceramic sealing ring.

[0004] To solve the above technical problems, the technical solution adopted by the present invention is: an aluminum nitride ceramic sealing ring, comprising the following materials in parts by weight: 83-85 parts of aluminum nitride mixed powder and 15-17 parts of a binder; the aluminum nitride mixed powder comprises the following materials in parts by weight: 80-85 parts of aluminum nitride powder, 3-7 parts of yttrium oxide and 1-2 parts of a dispersant; the binder comprises the following materials in parts by weight: 50-60 parts of paraffin, 3-6 parts of microcrystalline wax, 20-30 parts of high-density polyethylene, 8-15 parts of polypropylene and 3-6 parts of stearic acid.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing an aluminum nitride ceramic sealing ring, using the above aluminum nitride ceramic sealing ring, comprising the following steps: (1) preparing an aluminum nitride mixed powder; (2) mixing the aluminum nitride mixed powder and a binder in step (1) in proportion and kneading them into a feeding mass; (3) crushing the kneaded feeding mass into particles using a crusher; (4) filling a mold with an injection molding machine to obtain a product green body; (5) placing the injection product green body in an n-heptane solvent to remove most of the paraffin binder; (6) placing the degreased product in a debinding furnace for thermal degreasing to remove the remaining binder; and (7) placing the debinding green body in a vacuum graphite furnace and filling it with nitrogen for sintering.

[0006] Preferably, the preparation of aluminum nitride mixed powder specifically includes the following steps: mixing aluminum nitride powder, sintering aid yttrium oxide powder, and castor oil dispersant by ball milling in alcohol, drying, and sieving to obtain mixed powder.

[0007] Preferably, the mixing and kneading specifically comprises the following steps: putting the mixed powder and the binder component into a kneading machine for kneading at a mixing temperature of 180° C., a rotation speed of 30-40 rpm, and a time of 2-3 hours.

[0008] Preferably, the green body molding of the product specifically includes the following steps: using an injection molding machine to fill the mold to obtain a green body of the product, the injection temperature is 160°C-170°C, the injection pressure is 50-70Bar, the injection speed is 40-50mm / s, the holding pressure is 30-40Bar, and the holding time is 1-2s.

[0009] Preferably, the thermal degreasing specifically comprises the following steps: placing the green body of the product in n-heptane and heating it in a water bath at a temperature of 40-45°C.

[0010] Preferably, the debinding specifically includes the following steps: placing the dried green body into a debinding furnace for debinding, using a heating rate of 1°C / min before room temperature -120°C, a heating rate of 0.6°C / min at 120-200°C, a heating rate of 0.3°C / min at 200-400°C, a heating rate of 0.5°C / min at 400-500°C, and keeping at 500°C for 6 hours.

[0011] Preferably, the sintering specifically includes the following steps: placing the green body into a BN crucible, sintering in a vacuum graphite sintering furnace, introducing nitrogen, sintering at a temperature of 1750-1800° C., and keeping the temperature for 2-3 hours.

[0012] Compared with the prior art, the present invention has the following beneficial effects: paraffin is used as a flow carrier in the present invention, and a small amount of microcrystalline wax is added, which has suitable viscosity, high strength and good toughness; high-density polyethylene and polypropylene are selected as the skeleton binder of the high molecular polymer, which has high strength and plays a role in maintaining the shape of the blank and preventing deformation after the solvent degreasing and paraffin removal; in the thermal degreasing stage, the debinding temperature range of the product is widened, so that the product debinding process can be carried out slowly in multiple stages, thereby improving the debinding yield and shortening the debinding time. Stearic acid is used as a surfactant to improve the mixing uniformity of aluminum nitride powder and binder components and prevent the two phases from separating.

[0013] The green body produced has high strength, good shape retention, no defects in degreasing and debinding, good feeding fluidity, easy injection molding, easy to realize automated production, and can solve problems such as chipping and cracking caused by low green body strength; small sintering deformation, high dimensional accuracy, low internal porosity, greatly improving product performance, and high mass production efficiency. DETAILED DESCRIPTION

[0014] In order to make the above features and advantages of the present invention more obvious and easy to understand, embodiments are given below for detailed description. Example 1

[0015] An aluminum nitride ceramic sealing ring comprises the following materials in parts by weight: 83-85 parts of aluminum nitride mixed powder and 15-17 parts of a binder; the aluminum nitride mixed powder comprises the following materials in parts by weight: 80-85 parts of aluminum nitride powder, 3-7 parts of yttrium oxide and 1-2 parts of a dispersant; the binder comprises the following materials in parts by weight: 53 parts of paraffin wax, 6 parts of microcrystalline wax, 22 parts of high-density polyethylene, 14 parts of polypropylene and 5 parts of stearic acid.

[0016] The adhesive component uses paraffin as a main filler, a small amount of microcrystalline wax as a paraffin modifier to improve its plasticity, a mixture of high-density polyethylene and polypropylene as a skeleton material, and a small amount of stearic acid as a surfactant or lubricant.

[0017] A method for preparing an aluminum nitride ceramic sealing ring, using the aluminum nitride ceramic sealing ring, comprises the following steps: (1) preparing an aluminum nitride mixed powder; (2) mixing the aluminum nitride mixed powder in step (1) and a binder in proportion and kneading them to form a feeding mass; (3) crushing the kneaded feeding mass into particles using a crusher; (4) filling a mold with an injection molding machine to obtain a product green body; (5) placing the injection product green body in an n-heptane solvent to remove most of the paraffin binder; (6) placing the degreased product in a debinding furnace for thermal degreasing to remove the remaining binder; and (7) placing the debinding green body in a vacuum graphite furnace and filling it with nitrogen for sintering.

[0018] In this embodiment, the preparation of aluminum nitride mixed powder specifically includes the following steps: weighing 1000g of aluminum nitride powder, 40g of yttrium oxide powder as a sintering aid, and 10g of castor oil dispersant, ball-milling and mixing in alcohol, drying and sieving to obtain a mixed powder.

[0019] In this embodiment, the mixing and kneading specifically includes the following steps: the mixed powder and the binder component are placed in a kneading machine for kneading, the kneading temperature is 180° C., the speed is 30-40 rpm, and the time is 2-3 hours. In order to make the raw materials mixed evenly during the kneading process, after the binder component is completely melted, the raw materials adhering to the rotor of the kneading machine can be separated from the rotor by raising and lowering the temperature to obtain sufficient kneading, so that the prepared feed has better uniformity.

[0020] The kneaded feed mass is crushed into small particles by a crusher to facilitate injection molding production.

[0021] In this embodiment, the green body molding of the product specifically includes the following steps: using an injection molding machine to fill the mold to obtain a green body of the product, the injection temperature is 160℃-170℃, the injection pressure is 50-70Bar, the injection speed is 40-50mm / s, the holding pressure is 30-40Bar, and the holding time is 1-2s. Products in this link are prone to defects. Low mold temperature can easily lead to uneven product color, material shortage, shrinkage, etc., and excessively high temperature can easily cause deformation. Using different front and rear mold temperatures, generally the front mold temperature is 50-60℃, and the rear mold temperature is 30-40℃, which can solve these problems well.

[0022] In this embodiment, the thermal degreasing specifically includes the following steps: placing the green body of the product in n-heptane and heating it in a water bath at a temperature of 40-45°C. The temperature should not be too high, otherwise the product will easily deform and bubble. Depending on the size of the product, it is generally soaked for 1-2 days. After solvent degreasing, take it out and dry it.

[0023] In this embodiment, the debinding process specifically includes the following steps: placing the dried green body into a debinding furnace for debinding, using a heating rate of 1°C / min before room temperature reaches -120°C, a heating rate of 0.6°C / min at 120-200°C, a heating rate of 0.3°C / min at 200-400°C, a heating rate of 0.5°C / min at 400-500°C, and keeping at 500°C for 6 hours.

[0024] The setting of the debinding temperature curve can be achieved by testing the TG-DSC curve to analyze the decomposition temperature and volatilization temperature of the binder components. In the temperature range where each component undergoes drastic thermal weight loss, the heating rate should be set slower to prevent cracking and bubbling of the product.

[0025] In this embodiment, sintering specifically includes the following steps: placing the green body into a BN crucible, sintering in a vacuum graphite sintering furnace, introducing nitrogen, sintering at a temperature of 1750-1800° C., and keeping the temperature for 2-3 hours.

[0026] For products with high precision requirements, some dimensional accuracy cannot be achieved, and can be processed through double-sided grinding, internal and external cylindrical grinding, or precision carving and chamfering. Example 2

[0027] An aluminum nitride ceramic sealing ring comprises the following materials in parts by weight: 83-85 parts of aluminum nitride mixed powder and 15-17 parts of a binder; the aluminum nitride mixed powder comprises the following materials in parts by weight: 80-85 parts of aluminum nitride powder, 3-7 parts of yttrium oxide and 1-2 parts of a dispersant; the binder comprises the following materials in parts by weight: 55 parts of paraffin wax, 5 parts of microcrystalline wax, 27 parts of high-density polyethylene, 10 parts of polypropylene and 3 parts of stearic acid.

[0028] The adhesive component uses paraffin as a main filler, a small amount of microcrystalline wax as a paraffin modifier to improve its plasticity, a mixture of high-density polyethylene and polypropylene as a skeleton material, and a small amount of stearic acid as a surfactant or lubricant.

[0029] A method for preparing an aluminum nitride ceramic sealing ring, using the aluminum nitride ceramic sealing ring, comprises the following steps: (1) preparing an aluminum nitride mixed powder; (2) mixing the aluminum nitride mixed powder in step (1) and a binder in proportion and kneading them to form a feeding mass; (3) crushing the kneaded feeding mass into particles using a crusher; (4) filling a mold with an injection molding machine to obtain a product green body; (5) placing the injection product green body in an n-heptane solvent to remove most of the paraffin binder; (6) placing the degreased product in a debinding furnace for thermal degreasing to remove the remaining binder; and (7) placing the debinding green body in a vacuum graphite furnace and filling it with nitrogen for sintering.

[0030] In this embodiment, the preparation of aluminum nitride mixed powder specifically includes the following steps: weighing 1000g of aluminum nitride powder, 50g of yttrium oxide powder as a sintering aid, and 12g of castor oil dispersant, ball-milling and mixing in alcohol, drying and sieving to obtain a mixed powder.

[0031] In this embodiment, the mixing and kneading specifically includes the following steps: the mixed powder and the binder component are placed in a kneading machine for kneading, the kneading temperature is 180° C., the speed is 30-40 rpm, and the time is 2-3 hours. In order to make the raw materials mixed evenly during the kneading process, after the binder component is completely melted, the raw materials adhering to the rotor of the kneading machine can be separated from the rotor by raising and lowering the temperature to obtain sufficient kneading, so that the prepared feed has better uniformity.

[0032] The kneaded feed mass is crushed into small particles by a crusher to facilitate injection molding production.

[0033] In this embodiment, the green body molding of the product specifically includes the following steps: using an injection molding machine to fill the mold to obtain a green body of the product, the injection temperature is 160℃-170℃, the injection pressure is 50-70Bar, the injection speed is 40-50mm / s, the holding pressure is 30-40Bar, and the holding time is 1-2s. Products in this link are prone to defects. Low mold temperature can easily lead to uneven product color, material shortage, shrinkage, etc., and excessively high temperature can easily cause deformation. Using different front and rear mold temperatures, generally the front mold temperature is 50-60℃, and the rear mold temperature is 30-40℃, which can solve these problems well.

[0034] In this embodiment, the thermal degreasing specifically includes the following steps: placing the green body of the product in n-heptane and heating it in a water bath at a temperature of 40-45°C. The temperature should not be too high, otherwise the product will easily deform and bubble. Depending on the size of the product, it is generally soaked for 1-2 days. After solvent degreasing, take it out and dry it.

[0035] In this embodiment, the debinding process specifically includes the following steps: placing the dried green body into a debinding furnace for debinding, using a heating rate of 1°C / min before room temperature reaches -120°C, a heating rate of 0.6°C / min at 120-200°C, a heating rate of 0.3°C / min at 200-400°C, a heating rate of 0.5°C / min at 400-500°C, and keeping at 500°C for 6 hours.

[0036] The setting of the debinding temperature curve can be achieved by testing the TG-DSC curve to analyze the decomposition temperature and volatilization temperature of the binder components. In the temperature range where each component undergoes drastic thermal weight loss, the heating rate should be set slower to prevent cracking and bubbling of the product.

[0037] In this embodiment, sintering specifically includes the following steps: placing the green body into a BN crucible, sintering in a vacuum graphite sintering furnace, introducing nitrogen, sintering at a temperature of 1750-1800° C., and keeping the temperature for 2-3 hours.

[0038] For products with high precision requirements, some dimensional accuracy cannot be achieved, and can be processed through double-sided grinding, internal and external cylindrical grinding, or precision carving and chamfering. Example 3

[0039] An aluminum nitride ceramic sealing ring comprises the following materials in parts by weight: 83-85 parts of aluminum nitride mixed powder and 15-17 parts of a binder; the aluminum nitride mixed powder comprises the following materials in parts by weight: 80-85 parts of aluminum nitride powder, 3-7 parts of yttrium oxide and 1-2 parts of a dispersant; the binder comprises the following materials in parts by weight: 57 parts of paraffin wax, 3 parts of microcrystalline wax, 25 parts of high-density polyethylene, 10 parts of polypropylene and 5 parts of stearic acid.

[0040] The adhesive component uses paraffin as a main filler, a small amount of microcrystalline wax as a paraffin modifier to improve its plasticity, a mixture of high-density polyethylene and polypropylene as a skeleton material, and a small amount of stearic acid as a surfactant or lubricant.

[0041] A method for preparing an aluminum nitride ceramic sealing ring, using the aluminum nitride ceramic sealing ring, comprises the following steps: (1) preparing an aluminum nitride mixed powder; (2) mixing the aluminum nitride mixed powder in step (1) and a binder in proportion and kneading them to form a feeding mass; (3) crushing the kneaded feeding mass into particles using a crusher; (4) filling a mold with an injection molding machine to obtain a product green body; (5) placing the injection product green body in an n-heptane solvent to remove most of the paraffin binder; (6) placing the degreased product in a debinding furnace for thermal degreasing to remove the remaining binder; and (7) placing the debinding green body in a vacuum graphite furnace and filling it with nitrogen for sintering.

[0042] In this embodiment, the preparation of aluminum nitride mixed powder specifically includes the following steps: weighing 1000g of aluminum nitride powder, 70g of yttrium oxide powder as a sintering aid, and 15g of castor oil dispersant, ball-milling and mixing in alcohol, drying and sieving to obtain a mixed powder.

[0043] In this embodiment, the mixing and kneading specifically includes the following steps: the mixed powder and the binder component are placed in a kneading machine for kneading, the kneading temperature is 180° C., the speed is 30-40 rpm, and the time is 2-3 hours. In order to make the raw materials mixed evenly during the kneading process, after the binder component is completely melted, the raw materials adhering to the rotor of the kneading machine can be separated from the rotor by raising and lowering the temperature to obtain sufficient kneading, so that the prepared feed has better uniformity.

[0044] The kneaded feed mass is crushed into small particles by a crusher to facilitate injection molding production.

[0045] In this embodiment, the green body molding of the product specifically includes the following steps: using an injection molding machine to fill the mold to obtain a green body of the product, the injection temperature is 160℃-170℃, the injection pressure is 50-70Bar, the injection speed is 40-50mm / s, the holding pressure is 30-40Bar, and the holding time is 1-2s. Products in this link are prone to defects. Low mold temperature can easily lead to uneven product color, material shortage, shrinkage, etc., and excessively high temperature can easily cause deformation. Using different front and rear mold temperatures, generally the front mold temperature is 50-60℃, and the rear mold temperature is 30-40℃, which can solve these problems well.

[0046] In this embodiment, the thermal degreasing specifically includes the following steps: placing the green body of the product in n-heptane and heating it in a water bath at a temperature of 40-45°C. The temperature should not be too high, otherwise the product will easily deform and bubble. Depending on the size of the product, it is generally soaked for 1-2 days. After solvent degreasing, take it out and dry it.

[0047] In this embodiment, the debinding process specifically includes the following steps: placing the dried green body into a debinding furnace for debinding, using a heating rate of 1°C / min before room temperature reaches -120°C, a heating rate of 0.6°C / min at 120-200°C, a heating rate of 0.3°C / min at 200-400°C, a heating rate of 0.5°C / min at 400-500°C, and keeping at 500°C for 6 hours.

[0048] The setting of the debinding temperature curve can be achieved by testing the TG-DSC curve to analyze the decomposition temperature and volatilization temperature of the binder components. In the temperature range where each component undergoes drastic thermal weight loss, the heating rate should be set slower to prevent cracking and bubbling of the product.

[0049] In this embodiment, sintering specifically includes the following steps: placing the green body into a BN crucible, sintering in a vacuum graphite sintering furnace, introducing nitrogen, sintering at a temperature of 1750-1800° C., and keeping the temperature for 2-3 hours.

[0050] For products with high precision requirements, some dimensional accuracy cannot be achieved, and can be processed through double-sided grinding, internal and external cylindrical grinding, or precision carving and chamfering.

[0051] Flexural strength, tensile strength and air tightness tests The flexural strength of the aluminum nitride ceramic sealing ring materials prepared in Examples 1-3 was tested by the method provided in GB / T3001-2007. The tensile strength of the aluminum nitride ceramic sealing ring materials obtained in Examples 1-3 was tested by the method provided in GB / T228-1987. The air tightness of the aluminum nitride ceramic sealing ring was tested by the method provided in SJ / T11583-2016. The test results are shown in Table 1.

[0052] Table 1

[0053] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equalization change and modification made to the above embodiment by any technician familiar with the field without departing from the content of the technical solution of the present invention according to the technical essence of the present invention shall fall within the scope of the present invention.

Claims

1. An aluminum nitride ceramic sealing ring, characterized in that: It includes the following materials in parts by weight: 83-85 parts of aluminum nitride mixed powder and 15-17 parts of a binder; the aluminum nitride mixed powder includes the following materials in parts by weight: 80-85 parts of aluminum nitride powder, 3-7 parts of yttrium oxide and 1-2 parts of a dispersant; the binder includes the following materials in parts by weight: 50-60 parts of paraffin, 3-6 parts of microcrystalline wax, 20-30 parts of high-density polyethylene, 8-15 parts of polypropylene and 3-6 parts of stearic acid.

2. A method for preparing an aluminum nitride ceramic sealing ring, using the aluminum nitride ceramic sealing ring as claimed in claim 1, characterized in that: The method comprises the following steps: (1) preparing an aluminum nitride mixed powder; (2) mixing the aluminum nitride mixed powder and a binder in a certain proportion and kneading them into a feed mass; (3) crushing the kneaded feed mass into particles by a crusher; (4) filling a mold with an injection molding machine to obtain a green body; (5) placing the green body of the injection product in an n-heptane solvent to remove most of the paraffin binder; (6) placing the debinding product in a debinding furnace for thermal debinding to remove the remaining binder; and (7) placing the debinding body in a vacuum graphite furnace and filling it with nitrogen for sintering.

3. The method for preparing an aluminum nitride ceramic sealing ring according to claim 2, characterized in that: The preparation of aluminum nitride mixed powder specifically includes the following steps: aluminum nitride powder, sintering aid yttrium oxide powder, and castor oil dispersant are ball-milled and mixed in alcohol, and then dried and sieved to obtain mixed powder.

4. The method for preparing an aluminum nitride ceramic sealing ring according to claim 2, characterized in that: The mixing and kneading specifically includes the following steps: putting the mixed powder and the binder component into a kneading machine for kneading at a mixing temperature of 180° C., a rotation speed of 30-40 rpm, and a time of 2-3 hours.

5. The method for preparing an aluminum nitride ceramic sealing ring according to claim 2, characterized in that: The green body molding of the product specifically includes the following steps: using an injection molding machine to fill the mold to obtain the green body of the product, the injection temperature is 160℃-170℃, the injection pressure is 50-70Bar, the injection speed is 40-50mm / s, the holding pressure is 30-40Bar, and the holding time is 1-2s.

6. The method for preparing an aluminum nitride ceramic sealing ring according to claim 2, characterized in that: The thermal debinding specifically includes the following steps: placing the green body of the product in n-heptane and heating it in a water bath at a temperature of 40-45°C.

7. The method for preparing an aluminum nitride ceramic sealing ring according to claim 2, characterized in that: The debinding process specifically includes the following steps: placing the dried green body into a debinding furnace for debinding, using a heating rate of 1°C / min before room temperature -120°C, a heating rate of 0.6°C / min at 120-200°C, a heating rate of 0.3°C / min at 200-400°C, a heating rate of 0.5°C / min at 400-500°C, and keeping at 500°C for 6 hours.

8. The method for preparing an aluminum nitride ceramic sealing ring according to claim 2, characterized in that: The sintering specifically includes the following steps: placing the green body into a BN crucible, sintering in a vacuum graphite sintering furnace, introducing nitrogen, sintering at a temperature of 1750-1800° C., and keeping the temperature for 2-3 hours.

Citation Information

Patent Citations

  • Adhesive agent for injection molding of aluminum nitride ceramic and application method of adhesive agent

    CN104860684A

  • Adhesive for ceramic injection moulding and preparation method thereof

    CN108218441A

  • Binder as well as preparation method and application thereof

    CN111763090A

  • Method for producing components and parts made of aluminium nitride ceramics in high thermal conductivity and high dimensional accuracy

    CN1686942A

  • Microwave ceramic dielectric filter and processing and forming method therefor

    WO2021227603A1

Cited By

  • Carbon fiber reinforced carbonitride ceramic matrix high-temperature sealing material, preparation method and application

    CN122831717A